If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -9i) + (6 + -2i) = 0 Remove parenthesis around (3 + -9i) 3 + -9i + (6 + -2i) = 0 Remove parenthesis around (6 + -2i) 3 + -9i + 6 + -2i = 0 Reorder the terms: 3 + 6 + -9i + -2i = 0 Combine like terms: 3 + 6 = 9 9 + -9i + -2i = 0 Combine like terms: -9i + -2i = -11i 9 + -11i = 0 Solving 9 + -11i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -11i = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -11i = 0 + -9 -11i = 0 + -9 Combine like terms: 0 + -9 = -9 -11i = -9 Divide each side by '-11'. i = 0.8181818182 Simplifying i = 0.8181818182
| 4(-x-4)=20 | | 7-3x=5x-5 | | 4(3s+9)=168 | | 6(2k+1)-6k-2=14.016 | | 180-8x+2= | | 0=3/4x+3 | | -3n-6=15 | | 16x^2-2=79 | | 4(2l+1)=84 | | (6-2i)+(11+6i)=0 | | 20x-80y=0forY | | 70+60(8x+2)= | | 3(a-6)=42 | | y/2.5=5 | | xsquared+3x-8=0 | | -8(2t+1)=-24 | | (4-6i)(6-8i)=0 | | m/5-2=-12 | | -3(3x-5)=-14 | | 3(f-9)=-18 | | 3t+8=52 | | 3=-2+25 | | x*x-1x-12=0 | | x^3-bx^2-c=0 | | x/3+1=x/2-3 | | 5.9a+10=80.8 | | x+19=2x+19 | | K^2-4k-32=0 | | 14-5x=8-2x | | -9(-x-4)=-45 | | ax^3-bx^2-c=0 | | 48=5f+23 |